Downregulation of HDAC3 by ginsenoside Rg3 inhibits epithelial–mesenchymal transition of cutaneous squamous cell carcinoma through c‐Jun acetylation. Issue 12 (13th June 2019) - Zhang, Li; Shan, Xiu; Chen, Qun; Xu, Dayu; Fan, Xinling; Yu, Ming; Yan, Qiu; Liu, Jiwei
Abstract: The metastatic rate of human cutaneous squamous cell carcinoma (CSCC) has increased in recent years. Despite the current advances in therapies, effective treatments remain lacking. Ginsenoside 20(R)‐Rg3 is an effective antitumor monomer extracted from ginseng, but the role of Rg3 in CSCC remains unknown. It has been reported that aberrantly elevated histone deacetylase 3 (HDAC3) is involved in tumor malignancy in multiple malignant tumors. However, the effects of HDAC3 on the regulation of c‐Jun acetylation in tumor epithelial–mesenchymal transition (EMT) and migration have not been clearly illuminated. In our research, the immunohistochemistry staining results of skin tissue microarrays showed that HDAC3 staining was increased in CSCC compared with the normal dermal tissue. Then, we found that Rg3 treatment (25 and 50 μg/ml) inhibited CSCC cell (A431 and SCC12 cells) EMT through increasing E‐cadherin and decreasing N‐cadherin, vimentin, and Snail expression. Wound‐healing and transwell assays showed that Rg3 could inhibit migration. Meanwhile, Rg3 significantly downregulated the expression of HDAC3 in CSCC cells as detected by real‐time quantitative PCR, western blot, and immunofluorescence. Importantly, c‐Jun acetylation was increased by the downregulation of HDAC3 with HDAC3 shRNA, and the downregulation was associated with CSCC cell EMT inhibition. Collectively, our results showed that downregulation of HDAC3 by Rg3 or shHDAC3 treatment resulted in c‐Jun acetylation, which in turn inhibited CSCC cell EMT. These results indicate that HDAC3 could potentially serve as a therapeutic target therapeutic target for CSCC. Rg3 is an attractive and efficient agent that has oncotherapeutic effects and requires further investigation. Abstract : (1) Downregulation of histone deacetylase 3 (HDAC3) expression can increase the acetylation of c‐Jun. (2) The acetylation of c‐Jun can inhibit cutaneous squamous cell carcinoma epithelial–mesenchymal transition (EMT). (3) HDAC3 can be a potential therapeutic target for the treatment of cutaneous squamous cell carcinoma. (4) Ginsenoside 20 (R)‐Rg3 targeting at HDAC3 as an effective, low‐toxic inhibitor can be a new drug for adjuvant therapy of cutaneous squamous cell carcinoma.